Protective Effect of aqueous bark extract of Terminalia Arjuna against Alcohol-Induced Hepato and Nephrotoxicity in Rats - Ananda Vardhan Hebbani; vaddi Damodara Reddy; N Ch Varadacharyulu (International Journal of Phytomedicine, 2015)
Present study is an attempt to forward a locally available aqueous bark powder extract of Terminalia arjuna (AETA) as potential therapeutic agent against alcohol-induced oxidative/nitrosative stress mediated hepato and nephrotoxicity in rats. Alcohol administration significantly raised the plasma concentrations of nitrogenous compounds and increased activities of alcoholic marker enzymes, gamma glutamyl transferase (γGT), plasma transaminases (AST and ALT), alkaline phosphatase (ALP) and lactate dehydrogenase (LDH). Besides, we found abnormalities in the levels of plasma lipids, lipoproteins in alcohol administered rats along with increased lipid peroxidation and nitric oxide (NOx) levels. Moreover, significantly decreased hepatic and kidney antioxidant enzymes, superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and the content of reduced glutathione (GSH) in alcohol administered rats were noticed. Administration of AETA to alcoholic rats significantly brought these alterations in plasma to normal and also significantly reduced the levels of lipid peroxidation and restored the enzymic and nonenzymatic antioxidants in liver. These findings were further confirmed by hepatic and kidney histopathological studies. Co-administration of alcohol along with AETA offers protective effect against alcohol-induced stress and these protective effects are due to its multiple actions of its bioactive compounds.